Kegiatan Taman Pemulihan Gizi (TPG) terhadap Peningkatan Status Gizi Balita - Mamik Ratnawati; Rini Hayu Lestari; Septi Fitrah Ningtyas (Universitas STRADA Indonesia, 2018)
The nutritional status of children is one indicator that describes the level of nutritional status of the community. The type of research used is observational analytic research with comparative research design. The sample in this research is children less nutrition and uncomplicated malnutrition in Jatiwates village and Sentul village, Tembelang sub-district, Jombang regency with 11 children. The sampling technique used in this study is total sampling. The dependent variable in this research is the nutritional status of children. The independent variable in this research is Nutrition Recovery Park activity. Data analysis in this research use t-test. The results showed that there is influence of Nutrition Recovery Park activities with nutritional status of children. To further optimize the activities should equip APE facilities in order to improve the development of toddlers.